1998
DOI: 10.1002/(sici)1097-0339(199806)18:6<409::aid-dc5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Needle aspiration cytology of metastatic high-grade transitional-cell carcinomas of the urinary tract

Abstract: We reviewed 4 cases of high‐grade transitional‐cell carcinoma (TCC) of the urinary tract with solitary pulmonary metastases that were studied by transthoracic needle aspiration biopsy cytology. There were two grade II and two grade III TCCs. The two grade II tumors yielded, in needle aspirates, syncytial tumor‐cell clusters showing ill‐defined, granular cytoplasm and slightly pleomorphic nuclei with inconspicuous nucleoli. In one case the tumor‐cell clusters showed a focal acinar arrangement, mimicking cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Urothelial carcinoma is one of the most common malignancies that manifests as a solitary mass when it metastasizes . This poses a diagnostic challenge in long time smokers with history of UC who present with a solitary lung mass, because a new lung primary carcinoma is a possibility, as illustrated in the case we described.…”
Section: Discussionmentioning
confidence: 92%
“…Urothelial carcinoma is one of the most common malignancies that manifests as a solitary mass when it metastasizes . This poses a diagnostic challenge in long time smokers with history of UC who present with a solitary lung mass, because a new lung primary carcinoma is a possibility, as illustrated in the case we described.…”
Section: Discussionmentioning
confidence: 92%
“…We observed that, independent of the grade of the primary tumors, the smears showed numerous cercarifom cells with varied morphology, as described by Renshaw and Madge. 5 Thus, the paper of Ho et al 1 is amazing because the authors say not to observe cercariform cells, but they illustrated some of these in their Figure 1A. They report four cases of pulmonary metastatic high-grade TCC evaluated by FNAB.…”
mentioning
confidence: 99%
“…I read with great interest the paper of Ho et al 1 about metastatic high-grade transitional-cell carcinomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Those tumors consisted of two grade II and two grade III TCCs. In each case, 4-6 direct smears were prepared from the FNA, and they were stained by the Papanicolaou method.…”
mentioning
confidence: 99%